1981
DOI: 10.1128/iai.34.3.957-969.1981
|View full text |Cite
|
Sign up to set email alerts
|

Antagonisms among isogenic strains of Escherichia coli in the digestive tracts of gnotobiotic mice

Abstract: We have observed that antagonisms occur between isogenic strains of Escherichia coli associated with gnotobiotic mice. The strains differed in the carriage of plasmids or in chromosomal mutations. The plasmid-free strains, in general, inhibited the establishment of plasmid-bearing strains in the gastrointestinal tract of mice. The outcome of the interactions between isogenic pairs, however, depended on the order in which the strains were introduced into the mice. Maintaining the bacterial strains in monoassoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…ESBL-or PMQR-positive E. coli might have constituted either the predominant population of E. coli in the intestine of particular zoo animals or might have been transient flora. Duval-Iflah et al (1981) showed that indigenous flora that was adapted to host intestine was the dominant population and exerted a barrier against the establishment of externally introduced E. coli strains. However, even the transient presence of MDR E. coli harbouring conjugative ESBL-or PMQR-carrying plasmids might be of particular concern.…”
Section: Discussionmentioning
confidence: 99%
“…ESBL-or PMQR-positive E. coli might have constituted either the predominant population of E. coli in the intestine of particular zoo animals or might have been transient flora. Duval-Iflah et al (1981) showed that indigenous flora that was adapted to host intestine was the dominant population and exerted a barrier against the establishment of externally introduced E. coli strains. However, even the transient presence of MDR E. coli harbouring conjugative ESBL-or PMQR-carrying plasmids might be of particular concern.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the 86 ability to transfer and to colonise the gut is dependent on both the plasmid and on the bacterial host strain. Previously we have shown that strain EMO represses the establishment of isogenic [20] and heterogenic E. coli strains [22] carrying R plasmids in the digestive tract of mice and in human babies. This result confirms this particular property of EMO and showed that this antagonistic effect extends to plasmid which conferred an ecological advantage when it was present in other strains (PG1 and UB281) in the gut of axenic and gnotobiotic HFF mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on gnotobiotic mice and piglets have shown that oral inoculation of the plasmid-free Escherichia coli EMO inhibited the establishment of plasmid-carrying E. coli in the digestive ecosystem (Duval-Iflah et al 1981). In a doubleblind placebo-controlled trial, a protection rate of 32·3% against diarrhoea was obtained for 1 year with the early implantation of E. coli EMO into human newborns (Fig-ueiredo et al 1996).…”
Section: Introductionmentioning
confidence: 99%